1977
DOI: 10.1139/v77-542
|View full text |Cite
|
Sign up to set email alerts
|

Mass and infrared spectra of some S4N4 complexes of group VIII metals

Abstract: IAN S. BUTLER and TSUTOMU SAWAI. Can. J. Chem. 55,3838 (1977). The mass and ir spectra of the complexes formed between S4N4 and MCI, (M = Ni, Co, Pd) in methanol solution have been investigated. The mass spectral data indicate that the stoichiometry of the complexes is M(S2N2H), and the principal fragmentation is the stepwise loss of S N units, as is the case for S4N4 itself. The ir spectra of the complexes show the presence of N-H groups and suggest cis-planar configurations for the S2N2H chelating ligands. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

1977
1977
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…Previously, it was found that for S 4 N 4 there should be both infrared (IR) and Raman (RA) spectra included in the splitting of the four degenerate bands of the 18 modes of vibration. [48,51,52] The four degenerate bands correspond most closely to normal mode 4(5), mode 7(8), mode 11 (12), and mode 16(17) and are shown in brackets in each case, see Table 1 and -orting Information S1…”
Section: Resultsmentioning
confidence: 99%
“…Previously, it was found that for S 4 N 4 there should be both infrared (IR) and Raman (RA) spectra included in the splitting of the four degenerate bands of the 18 modes of vibration. [48,51,52] The four degenerate bands correspond most closely to normal mode 4(5), mode 7(8), mode 11 (12), and mode 16(17) and are shown in brackets in each case, see Table 1 and -orting Information S1…”
Section: Resultsmentioning
confidence: 99%
“…The correlation of "B and 'H spin-lattice relaxation times with molecular structure has been studied for a number of carbaboranes and metallocarbaboranes. 28 From the "B work T I values for the carbaboranes are found to be longer than for the analogous mono-metallocarbaboranes which in turn have longer Tl values than the corresponding dimetallocarbaboranes. For example, in 2,4-C2B5H7, T , (in ms) is 38.6 for B(e) (using the same numbering scheme as in it is 2.86.…”
Section: An Analogous Equation (3)mentioning
confidence: 98%
“…Problems relating to positions for proton abstraction are illustrated in the reaction sequences (3)-(5). 28 Although the reaction between the triphenylphosphonium salt (16) and base involves abstraction of two a-protons from the side chain to give the ylide in which the phosphorus is exocyclic [equation (3)], the trimethyl compound reacts with abstraction of protons from separate methyl groups to give the compound (17) in which the phosphorus is in the ring. The bromide (18), however, does not react in the same way to give the ylide (19): instead initial proton abstraction seems to be from the 3-bromopropyl side chain, with formation of the cyclopropylphosphorus Although several examples are known in which the alkyl group R2 bears a siliconcontaining substituent, reactions between trimethyl-or triethyl-methylidenephosphorane and chloromethylsilane give the product (20; R = Me or Et).30 It appears, therefore, that the attack of the ylide carbon is on silicon rather than carbon, probably reflecting the decreased polarity of the C-Cl bond in SiH3CH2Cl compared with CH3CH2Cl.…”
Section: Ylidesmentioning
confidence: 99%
“…S4N4 (38)) and very weak peaks at 184 (S4N4+) and 198 (S4N,+) were observed. The infrared and Raman spectra of S5N, are summarized in the Experimental section.…”
mentioning
confidence: 97%